Public Wrongs and the Criminal Law - Lee, A (Springer Netherlands, 2013)
This paper is about how best to understand the notion of 'public wrongs' in the longstanding idea that crimes are public wrongs. By contrasting criminal law with the civil laws of torts and contracts, it argues that 'public wrongs' should not be understood merely as wrongs that properly concern the public, but more specifically as those which the state, as the public, ought to punish. It then briefly considers the implications that this has on criminalization. © 2013 Springer Science+Business Media Dordrecht.